If x = 3r - 4 and y = 3r + 2, which of the following expresses y in terms of x ?

A.) y = x + 2

B.) y = x + 6

C.) y = 9r + 14

D.) y = 6r - 2

E.) y = 3x + 14

A.) y = x + 2

B.) y = x + 6

C.) y = 9r + 14

D.) y = 6r - 2

E.) y = 3x + 14

If x = 3r - 4 and y = 3r + 2, then

3r + 2 is six more than 3r - 4, because

→

y is six more than x

**y is 6 more than the value of x**, because:3r + 2 is six more than 3r - 4, because

→

**3r - 4 + 6 = 3r + 2**

y is six more than x

**B.) y = x + 6****Ask Algebra House**